A physical and chemical double cross-linked MXene composite film and its preparation method and application

Through the physical and chemical dual crosslinking technology, an MXene composite film with excellent mechanical properties and oxidative stability was prepared, which solved the problem of insufficient mechanical properties and oxidative stability of MXene materials when assembled into macroscopic structures, achieved high conductivity and good electromagnetic shielding performance, and expanded its application prospects in multiple fields.

CN115873279BActive Publication Date: 2025-04-11SHANDONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111143208.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-28
Publication Date
2025-04-11
Estimated Expiration
2041-09-28

Smart Images

  • Figure CN115873279B_ABST
    Figure CN115873279B_ABST
Patent Text Reader

Abstract

A MXene composite film with physical and chemical double crosslinking and a preparation method and application thereof, the preparation method comprising the following steps: (1) mixing a MXene aqueous dispersion with a water-soluble polymer aqueous dispersion, dispersing the mixture uniformly, and obtaining a mixed aqueous dispersion; (2) removing the water solvent from the mixed aqueous dispersion, drying, and obtaining a physically crosslinked film sample; (3) placing the film sample in a crosslinking agent solution containing isocyanate, chemically crosslinking, and drying to obtain the MXene composite film with physical and chemical double crosslinking. The MXene composite film has excellent mechanical properties, oxidation resistance, hydrophobicity, water resistance, excellent electrical conductivity, and electromagnetic shielding function, the preparation method is simple, the production energy consumption and cost are low, and large-scale industrial applications can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanomaterials, and specifically relates to a preparation method and application of a physical and chemical dual-crosslinked MXene electromagnetic shielding composite film material. Background Art

[0002] Nanomaterials are materials that have at least one dimension at the nanometer level (0.1-100nm) in three-dimensional space, or are composed of these basic unit types. They have special small size effects, surface effects, and unique mechanical, electrical, optical and thermal properties, which leads to many novel and excellent functional properties of macroscopic materials assembled from nanomaterials, and have very broad application prospects in the fields of mechanics, electronics, optics, thermal and biology. How to achieve large-scale and large-scale production of macroscopic aggregate materials assembled from nanomaterials through flexible, low-cost and green preparation methods has always been the development focus and challenge of academia and industry.

[0003] Transition metal carbide MXene is a novel two-dimensional inorganic compound composed of transition metal carbides with a thickness of several atomic layers. 3 AlC 2 , Advanced Materials 23(2011)4248-4253] and others published papers on two-dimensional Ti 3 C 2Since the work of MXene, it has provided great potential for the construction of high-performance macrostructures due to its near-metallic high conductivity, excellent mechanical properties, large specific surface area, biocompatibility, and a large number of hydrophilic functional groups that make it dispersible in water to form a stable aqueous dispersion. Due to the excellent mechanical, electrical and thermal properties of MXenes, researchers have been enthusiastic about it, and a new chapter has been opened for its development. After ten years of development, MXenes have achieved significant results in preparation, structure, performance, and application. From the initial small-scale preparation in the laboratory to the current mass production, its research has attracted more and more attention. However, the weak gel ability of MXenes limits its assembly into a strong macrostructure. The mechanical properties of the prepared MXenes film are poor, which limits its practical use potential. In addition to the weak gel ability that limits the development of MXenes-based macrostructure applications, MXenes are sensitive to humid environments and can be oxidized to transition metal oxides within a few days. The oxidation process starts from the edge of the MXenes sheet and it depends on the size. For example, the smaller the sheet, the easier it is to be oxidized. As the two-dimensional layered structure decomposes, its properties such as conductivity, mechanical strength and functional properties are severely deteriorated. In recent years, researchers have made some progress in the anti-oxidation of MXenes, including dehydration and drying, storage at low temperature and inert gas atmosphere, and replacing organic solvents with aqueous solutions. In addition, adding ionic liquids such as imidazolium, sodium L-ascorbate and polyanion salts has also become a method to keep MXene sheets fresh. For example, if there is no protection, Ti 3 C 2 MXene will gradually oxidize and degrade into titanium dioxide and carbon. The addition of the antioxidant antico was able to protect the nanosheets from severe oxidation. In the presence of sodium L-ascorbate, the MXene solution remained stable after 21 days, while the slice structure of MXenes stored in water deteriorated.

[0004] Therefore, developing more effective methods to improve the mechanical strength and oxidation stability of MXene-based macrostructures is of great significance in practical applications. Worldwide, research on utilizing the advantages of this nanomaterial to achieve scalable production of high-performance, durable and practical products has always been a research focus and challenge in this field, and plays a leading role in the research and development of my country in this field. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a physical and chemical dual cross-linked MXene composite film and a preparation method and application thereof. The MXene composite film material has excellent mechanical properties, oxidation resistance, hydrophobicity, waterproofness, excellent electrical conductivity and electromagnetic shielding function, the preparation method is simple, the production energy consumption and cost are low, and large-scale industrial application can be realized.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a physicochemical dual cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method:

[0008] (1) mixing a MXene aqueous dispersion with a water-soluble polymer aqueous dispersion and dispersing them uniformly to obtain a mixed aqueous dispersion;

[0009] (2) removing the water solvent from the mixed aqueous dispersion and drying it to obtain a physically cross-linked MXene composite film sample;

[0010] (3) placing the film sample in a solvent containing a cross-linking agent, chemically cross-linking, and drying to obtain the physical and chemical dual cross-linked MXene composite film;

[0011] The MXene forms a conductive path in the MXene composite film.

[0012] The MXene composite film provided by the present invention fully combines the excellent electrical conductivity and electromagnetic shielding properties of MXene itself, so that the MXene composite film has high electrical conductivity and good electromagnetic shielding function.

[0013] Physical cross-linking of MXene with polymers significantly improves the interfacial interaction between MXene sheets. At the same time, chemical cross-linking agents further chemically cross-link the physically cross-linked MXene-based composite films. The -NCO groups in the chemical cross-linking agents react with hydroxyl groups on the surface of MXene and polymers to form covalent bonds between MXene and polymers. At the same time, the hydrophobic skeleton of the cross-linking agent has a modifying effect on the composite film, improving the oxidation stability, mechanical strength, hydrophobicity, and water resistance of the MXene composite film. Under the cross-linking effects of physical cross-linking and chemical cross-linking, the two-dimensional layered structure of MXene is more stable and not easy to decompose. Therefore, the mechanical strength, oxidation stability, and hydrophobicity of the MXene composite film are greatly improved.

[0014] Preferably, the MXene is a two-dimensional transition metal carbide, nitride or carbonitride.

[0015] Wherein, based on the total solid mass of the raw materials, the mass percentage content of MXene is 10-99%, for example, it can be 12%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, 92%, 95%, 97%, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0016] The mass percentage content of MXene in the MXene aqueous dispersion is 0.01-15%, for example, it can be 0.02%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 3%, 5%, 8%, 10%, 12% or 14%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0017] Preferably, the water-soluble polymer includes any one or a combination of at least two of cellulose, hydroxymethyl cellulose, carboxymethyl cellulose, lignin, starch, hydroxymethyl starch, acetic starch, plant glue, animal glue, polyacrylamide, polyvinyl pyrrolidone, waterborne polyurethane, polyacrylic acid, polyacrylate, polyvinyl alcohol (PVA), polyaniline, polylactic acid, polymaleic anhydride or polyethylene glycol, and is further preferably any one or a combination of at least two of cellulose, polyvinyl alcohol or waterborne polyurethane. Cellulose is preferably cellulose nanofiber. Cellulose nanofiber is a new type of green material with good flexibility and mechanical properties. By mixing and cross-linking it with MXene, the mechanical properties of the composite film are greatly improved.

[0018] As a preferred technical solution of the present invention, the polyvinyl alcohol, cellulose and other polymers as water-soluble polymers can improve the dispersibility of MXene in water, and further promote the physical cross-linking of MXene to form a strong MXene composite material.

[0019] Preferably, based on the total solid mass of the raw materials, the mass percentage of the water-soluble polymer is 0.01-80%, for example, it can be 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 32%, 35%, 48%, 50%, 52%, 55%, 60%, 70%, 75%, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0020] The cross-linking agent is isocyanate;

[0021] The isocyanate includes any one or a combination of at least two of polymethylene polyphenyl polyisocyanate (PMDI), diphenylmethane-4,4'-diisocyanate (4,4'-MDI), toluene-2,4-diisocyanate, and hexamethylene diisocyanate, etc., preferably PMDI.

[0022] The isocyanate and MXene-based composite films are chemically cross-linked, and the -NCO groups in the isocyanate molecules react with the -OH groups on MXene and polymers, greatly improving the oxidation stability, mechanical strength, hydrophobicity, and water resistance of the MXene composite film.

[0023] Preferably, based on the total solid mass of the raw materials, the mass percentage of the cross-linking agent is 0.1-50%, for example, it can be 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 30%, 40%, 50% and specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0024] In the present invention, the MXene composite film may also contain other components, such as functional fillers, additives, etc.; the functional fillers or additives are uniformly dispersed in the matrix composed of MXene.

[0025] Preferably, based on the total solid mass of the raw materials, the mass percentage of the functional filler is 0.1-80%, for example, it can be 0.2%, 0.5%, 0.8%, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 32%, 35%, 48%, 50%, 52%, 55%, 68%, 70%, 75%, and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0026] Preferably, the functional filler is a metal filler and / or a non-metal filler.

[0027] Preferably, the functional filler includes any one or a combination of at least two of carbon nanotubes, silver nanowires, silver microwires, copper nanowires, copper microwires, gold nanowires, gold microwires, carbon fibers, graphene, aluminum oxide, iron oxide, manganese oxide, silicon oxide, silicon carbide, and carbon black, and is further preferably any one or a combination of at least two of silver nanowires, silver microwires, and graphene.

[0028] In the present invention, the functional filler includes but is not limited to nanoscale or micrometer-scale functional particles, and the functional properties of the functional filler include but are not limited to electrical, thermal and mechanical properties. The introduction of the above functional filler enables the MXene composite film material to have a wider range of applications in the fields of structural materials, electronics and electrical engineering.

[0029] Preferably, the auxiliary agent includes any one or more combinations of antimicrobial agents, reinforcing agents, flame retardants, thickeners, compatibilizers, antioxidants or tackifiers.

[0030] Preferably, based on the total solid mass of the raw materials, the mass percentage of the additive is 0.01-50%, for example, it can be 0.03%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 0.8%, 1%, 3%, 5%, 7%, 9%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45% or 48%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0031] Preferably, the antimicrobial agent comprises chlorhexidine and / or polyhexamethylenebiguanide (PHMB).

[0032] In the present invention, the form and composition of the auxiliary agent include but are not limited to inorganic nanoparticles, inorganic micron particles, synthetic small molecules, polymers or biomolecules, etc., which are used in the MXene composite film material as flame retardants, thickeners, compatibilizers, antioxidants or tackifiers.

[0033] Preferably, the thickness of the MXene composite film is 0.5 to 900 μm, for example, 0.8 μm, 1.0 μm, 5.0 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 120 μm, 150 μm, 180 μm, 200 μm, 220 The present invention relates to a nanostructured carbon foam and a nanostructured carbon foam. The nanostructured carbon foam is preferably 0.8 to 100 μm, and more preferably 0.9 to 80 μm.

[0034] Preferably, the density of the MXene composite film is 500-5000 mg / cm 3 , for example, 520 mg / cm 3 、550mg / cm 3 、580mg / cm 3 、700mg / cm 3 、750mg / cm 3 、800mg / cm 3 、850mg / cm 3 、900mg / cm 3 、950mg / cm 3 、1000mg / cm 3 、1050mg / cm 3 、1200mg / cm 3 、1500mg / cm 3 、2000mg / cm 3 、2500mg / cm 3 、3000mg / cm 3 、3500mg / cm 3 , 4000mg / cm 3 or 4500mg / cm 3 , and specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and further preferably 700 to 3500 mg / cm 3 , more preferably 900 to 3000 mg / cm 3 .

[0035] In a second aspect, the present invention provides a method for preparing a MXene composite film having a physical and chemical dual crosslinking as described in the first aspect, the preparation method comprising the following steps:

[0036] (1) mixing a MXene aqueous dispersion with a water-soluble polymer aqueous dispersion and dispersing them uniformly to obtain a mixed aqueous dispersion;

[0037] (2) removing the aqueous solvent from the aqueous dispersion and drying it to obtain a physically cross-linked MXene composite film sample;

[0038] (3) placing the film sample in a solvent containing a cross-linking agent, performing chemical cross-linking, and drying to obtain the physical and chemical dual cross-linked MXene composite film.

[0039] In the preparation method provided by the present invention, a MXene aqueous dispersion and a water-soluble polymer aqueous dispersion are first mixed and dispersed evenly to form a mixed aqueous dispersion, and then the aqueous dispersion is dried to remove the water solvent to prepare a physically cross-linked MXene composite film to obtain a pretreated sample; the pretreated sample is placed in an organic solvent containing a cross-linking agent, subjected to a chemical cross-linking treatment, and dried to obtain the MXene composite film material.

[0040] The preparation method has a simple process, does not require a special atmosphere, pressure or temperature, and does not require the use of complex instruments and equipment, which greatly reduces energy consumption and equipment costs, and provides a new idea for the large-scale industrial production of oriented structured MXene composite film materials.

[0041] Preferably, the MXene is a transition metal carbide Ti 3 C 2 .

[0042] Preferably, the mass percentage of the dispersoid in the aqueous dispersion is 0.1-50%, for example, it can be 0.2%, 0.5%, 0.8%, 1%, 3%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45% or 48%, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0043] In the present invention, the "dispersoid" refers to other components in the aqueous dispersion except water.

[0044] In the present invention, the dispersion in step (1) can be assisted by magnetic stirring and / or ultrasound, so that each component is evenly dispersed in water.

[0045] Preferably, the drying temperature in step (2) is 15-90°C, for example, 16°C, 18°C, 20°C, 22°C, 25°C, 38°C, 50°C, 62°C, 75°C or 88°C, and more preferably 50°C.

[0046] Preferably, the cross-linking agent in step (3) is an isocyanate, and further, the isocyanate includes any one or a combination of at least two of polymethylene polyphenyl polyisocyanate (PMDI), diphenylmethane-4,4'-diisocyanate (4,4'-MDI), toluene-2,4-diisocyanate, and hexamethylene diisocyanate, etc., preferably PMDI;

[0047] Preferably, the organic solvent in step (3) comprises any one or a combination of acetonitrile, methyl hexanoate, acetone, hexane, ethyl acetate, hexyl acetate, butanone, toluene, octane, butyl acetate, cyclohexanone, hexyl formate, etc., preferably acetonitrile and methyl hexanoate. The reaction temperature is related to the boiling point of the selected organic solvent. High temperature can increase the reaction rate, generally 25°C to 120°C, preferably 70°C. The reaction time is 30min to 24h, depending on the desired degree of crosslinking and reaction temperature.

[0048] Preferably, the drying temperature in step (3) is 15-180°C, for example, it can be 18°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 175°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range, and it is further preferably 20-100°C.

[0049] Preferably, the drying time in step (3) is 0.1 to 24 h, for example, it can be 0.3 h, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h or 22 h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and it is further preferably 0.5 to 6 h.

[0050] In a third aspect, the present invention provides an application of the MXene composite film as described in the first aspect in electromagnetic shielding materials, electric heating materials, fireproof materials, waterproof materials, thermal conductive materials, sensing materials, electrode materials, biomedical materials, antibacterial materials or supporting materials.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] (1) The MXene composite film material provided by the present invention can form a conductive path by physical cross-linking of MXene, and has controllable thickness, high mechanical strength and flexibility, excellent electrical conductivity, good hydrophobic and waterproof properties, oxidation stability, solvent resistance, good electrical heating performance and high electromagnetic shielding performance, such as a shielding effectiveness of more than 70 dB in the X-band.

[0053] (2) The MXene composite film material also includes functional fillers, polymers and additives, and their contents can be adjusted according to application requirements, so that the MXene composite film material has a wider range of applications in the fields of mechanics, electricity, heat or biomedicine.

[0054] (3) The MXene composite film material provided by the present invention does not require special atmosphere, pressure and temperature, nor does it require complicated instruments and equipment. It has a simple preparation process and low operating cost, reduces energy consumption and equipment costs, can achieve large-scale production, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 An optical picture of the MXene composite film material provided in Example 1;

[0056] Figure 2 An optical picture of the bending display of the MXene composite film material provided in Example 1;

[0057] Figure 3 A cross-sectional scanning electron microscope image of the MXene composite film material provided in Example 1;

[0058] Figure 4 A graph showing the electrical conductivity test results of the MXene composite film material provided in Example 3;

[0059] Figure 5 A graph showing the test results of the electrical conductivity of the MXene composite film material provided in Example 3;

[0060] Figure 6 This is an optical picture showing the curling of the MXene composite film material provided in Example 5;

[0061] Figure 7 A graph showing the solvent resistance test results of the MXene composite film material provided in Example 6;

[0062] Figure 8 This is a surface contact angle test diagram of the MXene composite film material provided in Example 6;

[0063] Fig. 9 A diagram showing the waterproof test results of the MXene composite film material provided in Example 6;

[0064] Fig.10 This is a graph showing the oxidation stability results of the MXene composite film material provided in Example 6;

[0065] Fig.11 This is a graph showing the results of the electrothermal test of the MXene composite film material provided in Example 8;

[0066] Fig.12 This is a diagram of the electromagnetic shielding effectiveness of the MXene composite film material provided in Example 8. DETAILED DESCRIPTION

[0067] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0068] Example 1

[0069] A physical and chemical double cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method:

[0070] (1) Mixing a MXene aqueous dispersion with a cellulose nanofiber (diameter 3-5 nm, length 400 nm, Northern Century Cellulose Materials Co., Ltd.) aqueous dispersion and dispersing them evenly so that the mass percentage of the dispersoid in the mixed system is 0.75%, thereby obtaining a mixed aqueous dispersion;

[0071] (2) placing the mixed aqueous dispersion obtained in step (1) on a mold cast on polytetrafluoroethylene, placing it in an oven at 50° C. and drying it at normal pressure for 4 h to remove the water solvent and obtain a physically cross-linked MXene composite film as a pretreated sample;

[0072] (3) The pretreated sample obtained in step (2) is placed in a solvent containing PMDI, the solvent being a mixture of acetonitrile and methyl hexanoate (4:1, v / v), and a chemical crosslinking reaction is performed. The reaction time is 2 hours and the temperature is 70 degrees Celsius. After the reaction, the MXene composite film is dried to obtain the MXene composite film.

[0073] In this embodiment, based on the total solid mass of the raw materials, the mass percentage content of MXene is 80%, the mass percentage content of cellulose nanofibers is 15%, and the mass percentage content of PMDI is 5%.

[0074] The MXene is titanium carbide Ti 3 C 2 , which forms a conductive pathway in the MXene composite film.

[0075] The optical picture of the MXene composite film material is as follows Figure 1 As shown, according to Figure 1 It can be seen that the length of the MXene composite film material is about 10 cm, and the size of the MXene composite film material is controllable and can adapt to the requirements of different application fields. Figure 2 This is an optical picture of the bending display of the MXene composite film material. Figure 2 It can be seen that the material has good flexibility and bendability and is not easy to break.

[0076] The MXene composite film material provided in this embodiment was tested for microscopic morphology by scanning electron microscopy (SEM, JSM-7600F), and the obtained SEM image is as follows: Figure 3 As shown, the MXene layers observed in the MXene composite film material are stacked and interconnected to form a conductive path. Figure 3 It can be seen that the average thickness of the MXene composite film material is 8 μm.

[0077] Example 2

[0078] A physical and chemical double cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method:

[0079] (1) Mixing the MXene aqueous dispersion with the cellulose nanofiber (diameter 30-50 nm, length 500 nm, Northern Century Cellulose Materials Co., Ltd.) aqueous dispersion, dispersing them evenly, so that the mass percentage of the dispersoid in the mixed system is 0.75%, to obtain a mixed aqueous dispersion;

[0080] (2) placing the mixed aqueous dispersion obtained in step (1) on a mold cast on polytetrafluoroethylene, placing it in an oven at 50° C. and drying it at normal pressure for 4 h to remove the water solvent and obtain a physically cross-linked MXene composite film as a pretreated sample;

[0081] (3) The pretreated sample obtained in step (2) is placed in a solvent containing PMDI, the solvent being a mixture of acetonitrile and methyl hexanoate (4:1, v / v), and a chemical crosslinking reaction is performed. The reaction time is 3 hours and the temperature is 60° C. After the reaction, the MXene composite film is dried to obtain the MXene composite film.

[0082] In this embodiment, based on the total solid mass of the raw materials, the mass percentage content of MXene is 70%, the mass percentage content of cellulose nanofibers is 20%, and the mass percentage content of PMDI is 10%.

[0083] Example 3

[0084] A physical and chemical double cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method:

[0085] (1) mixing a MXene aqueous dispersion with a polyvinyl alcohol aqueous dispersion and dispersing them uniformly so that the mass percentage of the dispersoid in the mixed system is 50%, thereby obtaining a mixed aqueous dispersion;

[0086] (2) placing the mixed aqueous dispersion obtained in step (1) on a mold cast on polytetrafluoroethylene, placing it in an oven at 50° C. and drying it at normal pressure for 4 h to remove the water solvent and obtain a physically cross-linked MXene composite film as a pretreated sample;

[0087] (3) The pretreated sample obtained in step (2) is placed in a solvent containing MDI, the solvent being a mixture of acetonitrile and methyl hexanoate (4:1, v / v), and a chemical crosslinking reaction is performed. The reaction time is 3 hours and the temperature is 70° C. After the reaction, the MXene composite film is dried to obtain the MXene composite film.

[0088] The above MXene aqueous dispersion also contains carbon nanotubes.

[0089] In this embodiment, based on the total solid mass of the raw materials, the mass percentage content of MXene is 50%, the mass percentage content of polyvinyl alcohol is 30%, the mass percentage content of MDI is 5%, and the mass percentage content of carbon nanotubes is 15%.

[0090] The MXene is titanium carbide Ti 3 C 2 , which forms a conductive pathway in the MXene composite film.

[0091] The conductivity of the MXene composite film material provided in this embodiment was measured by a four-probe method using a Keithley 4200SCS semiconductor parameter analysis system. The obtained conductivity test graph is shown in FIG. Figure 4 As shown, the electrical conductivity of the MXene composite film material reaches 2000S / cm.

[0092] The conductive properties of the MXene composite film material provided in this embodiment were tested as follows: the MXene composite film material was connected in series with an LED lamp and a battery (1.5V). After the circuit was turned on, the LED lamp emitted light. The conductive properties test results were shown in the figure below. Figure 5 As shown, it is further demonstrated that the MXene composite film material has high electrical conductivity and can drive LED lights. At the same time, when the MXene composite film is bent, the LED lighting effect is not affected, proving the bending resistance of the MXene composite film.

[0093] Example 4

[0094] A physical and chemical double cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method:

[0095] (1) mixing a MXene aqueous dispersion with a polyurethane aqueous dispersion and dispersing them uniformly so that the mass percentage of the dispersoid in the mixed system is 50%, thereby obtaining a mixed aqueous dispersion;

[0096] (2) placing the mixed aqueous dispersion obtained in step (1) on a mold cast on polytetrafluoroethylene, placing it in an oven at 80° C. and drying it at normal pressure for 3.5 h to remove the water solvent and obtain a physically cross-linked MXene composite film as a pretreated sample;

[0097] (3) The pretreated sample obtained in step (2) is placed in a solvent containing MDI, the solvent being a mixture of acetonitrile and methyl hexanoate (4:1, v / v), and a chemical crosslinking reaction is performed. The reaction time is 3 hours and the temperature is 70° C. After the reaction, the MXene composite film is dried to obtain the MXene composite film.

[0098] The above-mentioned MXene aqueous dispersion also contains silver nanowires and an antioxidant.

[0099] In this embodiment, based on the total solid mass of the raw materials, the mass percentage content of MXene is 10%, the mass percentage content of polyurethane is 49%, the mass percentage content of MDI is 5%, the mass percentage content of silver nanowires is 35%, and the mass percentage content of antioxidant is 1%.

[0100] The MXene is titanium carbide Ti 3 C 2 , which forms a conductive pathway in the MXene composite film.

[0101] Example 5

[0102] A physical and chemical double cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method:

[0103] (1) mixing the MXene aqueous dispersion and the hydroxymethyl cellulose aqueous dispersion, dispersing them uniformly so that the mass percentage of the dispersoid in the mixed system is 50%, to obtain a mixed aqueous dispersion;

[0104] (2) placing the mixed aqueous dispersion obtained in step (1) on a mold cast on polytetrafluoroethylene, placing it in an oven at 50° C. and drying it at normal pressure for 4 h to remove the water solvent and obtain a physically cross-linked MXene composite film as a pretreated sample;

[0105] (3) The pretreated sample obtained in step (2) is placed in a solvent containing TDI, wherein the solvent is a mixture of acetonitrile and methyl hexanoate (4:1, v / v), and a chemical crosslinking reaction is performed. The reaction time is 3 hours and the temperature is 70° C. After the reaction, the MXene composite film is dried to obtain the MXene composite film.

[0106] In this embodiment, based on the total solid mass of the raw materials, the mass percentage content of MXene is 90%, the mass percentage content of hydroxymethyl cellulose is 5%, and the mass percentage content of TDI is 5%.

[0107] The MXene is titanium carbide Ti 3 C 2 , which forms a conductive pathway in the MXene composite film.

[0108] The mechanical properties of the MXene composite film material provided in this embodiment were tested, and the flexibility test results are shown in the figure below: Figure 6 As shown, the MXene composite film material can be rolled and wound without breaking and has excellent flexibility.

[0109] Example 6

[0110] A physical and chemical double cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method:

[0111] (1) mixing a MXene aqueous dispersion with a polyvinyl alcohol aqueous dispersion and dispersing them uniformly so that the mass percentage of the dispersoid in the mixed system is 5.5%, thereby obtaining a mixed aqueous dispersion;

[0112] (2) placing the mixed aqueous dispersion obtained in step (1) on a mold cast on polytetrafluoroethylene, placing it in an oven at 50° C. and drying it at normal pressure for 4 h to remove the water solvent and obtain a physically cross-linked MXene composite film as a pretreated sample;

[0113] (3) The pretreated sample obtained in step (2) is placed in a solvent containing PMDI, the solvent being a mixture of acetonitrile and methyl hexanoate (4:1, v / v), and a chemical crosslinking reaction is performed. The reaction time is 2 hours and the temperature is 80° C. After the reaction, the MXene composite film is dried to obtain the MXene composite film.

[0114] In this embodiment, based on the total solid mass of the raw materials, the mass percentage content of MXene is 80%, the mass percentage content of polyvinyl alcohol is 10%, and the mass percentage content of PMDI is 10%.

[0115] The MXene is titanium carbide Ti 3 C 2 , which forms a conductive pathway in the MXene composite film.

[0116] The solvent resistance of the MXene composite film material provided in this embodiment was tested, and the experimental solvents were ethanol and acetone. The test results are shown in the figure Figure 7 As shown, the MXene composite film material can maintain excellent stability after being immersed in ethanol and acetone for 30 days.

[0117] The surface water contact angle of the MXene composite film material provided in this embodiment is tested by a contact angle measuring instrument. The test diagram is as follows Figure 8As shown, the water contact angle is about 100°, indicating that the MXene composite film material has high hydrophobicity.

[0118] The MXene composite film prepared in this example and the MXene film without physical and chemical double crosslinking were placed in water and treated with ultrasound (100 W power) for 30 minutes. The experimental results are as follows: Fig. 9 The MXene film that has not undergone physical and chemical dual cross-linking has been completely decomposed, while the MXene composite film prepared in this embodiment is still intact, indicating that the MXene composite film prepared in this embodiment has good water resistance.

[0119] Example 7

[0120] A physical and chemical double cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method:

[0121] (1) mixing a MXene aqueous dispersion with a polyvinyl alcohol aqueous dispersion and dispersing them uniformly so that the mass percentage of the dispersoid in the mixed system is 4.5%, thereby obtaining a mixed aqueous dispersion;

[0122] (2) placing the mixed aqueous dispersion obtained in step (1) on a mold cast on polytetrafluoroethylene, placing it in an oven at 50° C. and drying it at normal pressure for 4 h to remove the water solvent and obtain a physically cross-linked MXene composite film as a pretreated sample;

[0123] (3) The pretreated sample obtained in step (2) is placed in a solvent containing PMDI, the solvent being acetone, to carry out a chemical crosslinking reaction. The reaction time is 4 hours and the temperature is 60° C. After the reaction, the MXene composite film is dried to obtain the MXene composite film.

[0124] In this embodiment, based on the total solid mass of the raw materials, the mass percentage content of MXene is 90%, the mass percentage content of polyvinyl alcohol is 6%, and the mass percentage content of PMDI is 4%.

[0125] The MXene is titanium carbide Ti 3 C 2 , which forms a conductive pathway in the MXene composite film.

[0126] The MXene composite film prepared in this example was subjected to an oxidation stability test with a MXene film that had not undergone physical and chemical dual crosslinking. The samples were placed at 70°C and 90% RH for 10 days. The results are as follows: Fig.10 As shown, the MXene film that has not undergone physical and chemical dual cross-linking has been broken, while the MXene composite film prepared in this example is relatively intact, which indicates that the MXene composite film prepared in this example has good oxidative stability.

[0127] Example 8

[0128] A physical and chemical double cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method:

[0129] (1) mixing the MXene aqueous dispersion and the cellulose nanofiber aqueous dispersion, dispersing them uniformly so that the mass percentage of the dispersoid in the mixed system is 0.6%, to obtain a mixed aqueous dispersion;

[0130] (2) placing the mixed aqueous dispersion obtained in step (1) on a mold cast on polytetrafluoroethylene, placing it in an oven at 80° C. and drying it at normal pressure for 3 h to remove the water solvent and obtain a physically cross-linked MXene composite film as a pretreated sample;

[0131] (3) The pretreated sample obtained in step (2) is placed in a solvent containing PMDI, the solvent being acetone, to carry out a chemical crosslinking reaction. The reaction time is 2 hours and the temperature is 100° C. After the reaction, the MXene composite film is dried to obtain the MXene composite film.

[0132] In this embodiment, based on the total solid mass of the raw materials, the mass percentage content of MXene is 67%, the mass percentage content of cellulose nanofibers is 22%, and the mass percentage content of PMDI is 11%.

[0133] The MXene is titanium carbide Ti 3 C 2 , which forms a conductive pathway in the MXene composite film.

[0134] The MXene composite film material provided in this embodiment is adhered to the electrode by silver glue, and the electrode spacing is 30 mm; voltage (4V, 6V, 8V, 10V respectively) is applied between the electrodes, and the point temperature is measured on the surface using a thermocouple, and the temperature and time are recorded and plotted. The electrothermal test results are shown in the figure below: Fig.11 As shown, from Fig.11 It can be seen that under different voltages, the MXene composite film material can rise to different temperatures and remain stable, and has the function of electrothermal generation at a lower voltage.

[0135] The electromagnetic shielding performance of the MXene composite film material provided in this embodiment was measured using a vector network analyzer (VNA, Agilent 8517A). The electromagnetic shielding effectiveness graph obtained is as shown in FIG. Fig.12 As shown, the MXene composite film material can have a shielding effectiveness of more than 70dB in the X-band (8.2-12.4GHz), and can attenuate electromagnetic waves by more than 99.999%, far exceeding the commercial requirement of 20dB.

[0136] Combined with the above embodiments, it can be seen that the preparation method of the MXene composite film material provided by the present invention is simple, has low operating costs, greatly saves equipment costs, and reduces energy consumption. The MXene composite film material has high electrical conductivity, excellent mechanical strength, flexibility, solvent resistance, and oxidation stability. Its surface is hydrophobic and has a waterproof effect. It can generate heat electrically and has good electric heating performance. It also has excellent electromagnetic shielding performance and has a shielding effectiveness of more than 70dB in the X-band. It can have broad application prospects in multiple fields such as mechanics, electricity, heat, or biomedicine.

[0137] The applicant declares that the present invention illustrates the MXene composite film material prepared at normal pressure and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A physical and chemical double cross-linked MXene composite film, wherein the MXene composite film is prepared by the following method: (1) Mixing the MXene aqueous dispersion and the water-soluble polymer aqueous dispersion and dispersing them evenly to obtain a mixed aqueous dispersion; (2) removing the water solvent from the mixed aqueous dispersion and drying it to obtain a physically cross-linked MXene composite film sample; (3) placing the film sample in an organic solvent containing a cross-linking agent to carry out a chemical cross-linking reaction, and drying to obtain the physical and chemical dual cross-linked MXene composite film; The MXene forms a conductive path in the MXene composite film; Based on the total solid mass of the raw materials, the mass percentage content of the MXene is 10-99%; the MXene is a carbide, nitride or carbonitride of a two-dimensional transition metal; Based on the total solid mass of the raw materials, the mass percentage content of the water-soluble polymer is 0.01-80%; The cross-linking agent is isocyanate, and the mass percentage content of the cross-linking agent is 0.1-50% based on the total solid mass of the raw materials; The water-soluble polymer includes any one of cellulose, polyvinyl alcohol or polyurethane, or a combination of at least two of them.

2. The MXene composite film according to claim 1, characterized in that The MXene is titanium carbide Ti3C2.

3. The MXene composite film according to claim 1, characterized in that The cellulose is cellulose nanofiber.

4. The MXene composite film according to claim 1, characterized in that The isocyanate includes any one of polymethylene polyphenyl polyisocyanate PMDI, diphenylmethane-4,4'-diisocyanate 4,4'-MDI, toluene-2,4-diisocyanate, and hexamethylene diisocyanate, or a combination of at least two thereof.

5. The MXene composite film according to claim 1, characterized in that The isocyanate is PMDI.

6. The MXene composite film according to claim 1, characterized in that The MXene aqueous dispersion further comprises one or two of a functional filler and an auxiliary agent. The auxiliary agent includes any one or more combinations of antimicrobial agents, reinforcing agents, flame retardants, thickeners, compatibilizers, antioxidants or tackifiers.

7. The MXene composite film according to claim 6, characterized in that Based on the total solid mass of the raw materials, the mass percentage of the functional filler is 0.1-80%.

8. The MXene composite film according to claim 6, characterized in that The functional filler is a metal filler and / or a non-metal filler.

9. The MXene composite film according to claim 6, characterized in that: The functional filler includes any one of carbon nanotubes, silver nanowires, silver microwires, copper nanowires, copper microwires, gold nanowires, gold microwires, carbon fibers, graphene, aluminum oxide, iron oxide, manganese oxide, silicon oxide, silicon carbide, and carbon black, or a combination of at least two thereof.

10. The MXene composite film according to claim 6, characterized in that: The functional filler is any one of carbon nanotubes, silver nanowires, silver microwires, and graphene, or a combination of at least two of them.

11. The MXene composite film according to claim 6, characterized in that The antibacterial agent includes one or two of chlorhexidine and polyhexanide hydrochloride PHMB.

12. The MXene composite film according to claim 6, characterized in that Based on the total solid mass of the raw materials, the mass percentage of the auxiliary agent is 0.01-50%.

13. The MXene composite film according to claim 1, characterized in that The thickness of the MXene composite film is 0.5~900 μm.

14. The MXene composite film according to claim 1, characterized in that The thickness of the MXene composite film is 0.8-100 μm.

15. The MXene composite film according to claim 1, characterized in that The thickness of the MXene composite film is 0.9~80 μm.

16. The MXene composite film according to claim 1, characterized in that The density of the MXene composite film is 500-5000 mg / cm 3 .

17. The MXene composite film according to claim 1, characterized in that The density of the MXene composite film is 700-3500 mg / cm 3 .

18. The MXene composite film according to claim 1, characterized in that The density of the MXene composite film is 900-3000 mg / cm 3 .

19. A method for preparing a MXene composite film according to any one of claims 1 to 18, characterized in that: The preparation method comprises the following steps: (1) Mixing the MXene aqueous dispersion and the water-soluble polymer aqueous dispersion and dispersing them evenly to obtain a mixed aqueous dispersion; (2) removing the water solvent from the mixed aqueous dispersion and drying it to obtain a physically cross-linked MXene composite film sample; (3) Placing the film sample in an organic solvent containing a cross-linking agent to carry out a chemical cross-linking reaction, and drying to obtain the physical and chemical dual cross-linked MXene composite film.

20. The preparation method according to claim 19, characterized in that: The mass percentage content of MXene in the MXene aqueous dispersion is 0.01-15%; the mass percentage content of the dispersoid in the mixed aqueous dispersion is 0.1-50%; the organic solvent includes any one or a combination of several of acetonitrile, methyl hexanoate, acetone, hexane, ethyl acetate, hexyl acetate, butanone, toluene, octane, butyl acetate, cyclohexanone, and hexyl formate.

21. The preparation method according to claim 19, characterized in that: The organic solvents are acetonitrile and methyl hexanoate.

22. A use of the MXene composite film according to any one of claims 1 to 18 in electromagnetic shielding materials, electric heating materials, fireproof materials, waterproof materials, thermal conductive materials, sensing materials, electrode materials or supporting materials.

23. Use of the MXene composite film according to any one of claims 1 to 18 in the preparation of biomedical materials or antibacterial materials.

Citation Information

Patent Citations

  • Preparing method of hydrophobic two-dimensional Ti3C2Tx-MXene thin film at normal temperature

    CN110171831A

  • Waterborne polyurethane-MXene electromagnetic shielding bionic nanocomposite material film and preparation method

    CN110698847A